KUALITAS KEPEMIMPINAN, ETOS MORALITAS PRIBADI, KOMPETENSI, DAN PELAYANAN PUBLIK - ', Dody Setyawan; ', Nanang Bagus.S (Jurnal Ilmu Administrasi Negara, 2014)
Ethos Private Morality, Competence, and the Public Service. This study aims to determine the effect of leadership qualities, personal moral ethics, and competence in the performance of public services in East Java legislators. The method used is a quantitative method. The study population was a community that metropolis, traditional and civil society. Sampling was stratified random sampling and purposive sampling with as many as 115 respondents. Data collection techniques using koesioner, interviews, and observations. Data were analyzed with path analysis method with SPSS software. The results showed that the ethos of personal morality and competence indirectly influence on legislators public service through leadership qualities. To improve the quality of public service leadership legislators in leading the people it represents needs to be improved. Keywords: performance, leadership qualities, personal morality ethics, competence, public service.